Produção leiteira no Paraná : um estudo considerando os efeitos espaciais - Capucho, Thaís Oliveira (2010)
The objective of this research is to study the spatial distribution of production of the dairy industry of cities of Paraná. To this end, we use the method of Exploratory Spatial Data Analysis (ESDA) by means of Moran's I statistics and the analysis of identification of clusters. The Moran's I statistic allows, for example, assess the degree of correlation between a region and its neighbors considering any variable of interest. Since the cluster analysis provides a simple view of a cluster of nearby regions on a map that have similar values, ie, allows the visualization of clusters if any. Through the development timeline can be seen that Paraná has achieved an extraordinary expansion of production and productivity, which exceed the national averages. The results point to the West, Southwest and Central and Eastern Parana as areas of highest value of production and productivity rates. In addition, there are also significant advances in genetics and herd management practices of the activity. The results demonstrate the regional differences of Parana in relation to dairy farming. The analysis indicates the heterogeneity among dairy farmers of the state. Thus, one can adopt more effective policies in each region, seeking to improve the development of municipalities and the state as a whole.